1993
DOI: 10.3382/ps.0720051
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Hydrated Sodium Calcium Aluminosilicate to Reduce the Toxicity of Aflatoxin and Diacetoxyscirpenol

Abstract: A hydrated sodium calcium aluminosilicate (HSCAS) was incorporated into diets (.5%) containing 3.5 mg/kg aflatoxin (AF) and 5.0 mg/kg diacetoxyscirpenol (DAS) singly and in combination. Male broiler chicks received ad libitum access to their respective diets and water from 1 to 21 days of age. Body weight gains were significantly (P < .05) depressed by AF and DAS singly and a synergistic interaction occurred between AF and DAS for a further depression of body weight gains. Alterations in hematological and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(57 citation statements)
references
References 27 publications
6
43
2
6
Order By: Relevance
“…Serum total lipids was reduce when chicks fed aflatoxicated diet. Similar results were reported by Kubena et al (1993a). This may be due to the interference of AF with lipid metabolism as those reported by Hamilton, and Garlich (1972) who explained that lipid transport is inhibited by aflatoxicosis which could account for the accumulation of lipid in the liver and their decreases in the serum, but the tow agents (0.2% Humate or 0.5% HSCAS) applied significantly counteracted the effect of AF.…”
Section: Biochemical Parameterssupporting
confidence: 79%
See 2 more Smart Citations
“…Serum total lipids was reduce when chicks fed aflatoxicated diet. Similar results were reported by Kubena et al (1993a). This may be due to the interference of AF with lipid metabolism as those reported by Hamilton, and Garlich (1972) who explained that lipid transport is inhibited by aflatoxicosis which could account for the accumulation of lipid in the liver and their decreases in the serum, but the tow agents (0.2% Humate or 0.5% HSCAS) applied significantly counteracted the effect of AF.…”
Section: Biochemical Parameterssupporting
confidence: 79%
“…The reduction in the total serum protein in aflatoxin fed group could referred to impairment of amino acid transport and mRNA transcription by inhibiting DNA (Kubena et al, 1993a) and is indicator of impaired protein synthesis (Kubena et al, 1998). Serum total lipids was reduce when chicks fed aflatoxicated diet.…”
Section: Biochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However Eser et al (10) reported that serum total protein was not affected by the usage of sepiolite in broiler diets. Some researchers determined that hydrated sodium calcium aluminosilicates did not result in any significant changes in serum chemistry in trials with chicks (4,8,13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, alguns adsorventes podem prejudicar a utilização de nutrientes e apresentam taxa de inclusão elevada nas dietas (Kubena et al, 1993;Parlat et al, 1999;Maiazzo et al, 2000;Rosa et al, 2001).…”
Section: Introductionunclassified